5X+Y-3Z=1

Simple and best practice solution for 5X+Y-3Z=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5X+Y-3Z=1 equation:


Simplifying
5X + Y + -3Z = 1

Solving
5X + Y + -3Z = 1

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1Y' to each side of the equation.
5X + Y + -1Y + -3Z = 1 + -1Y

Combine like terms: Y + -1Y = 0
5X + 0 + -3Z = 1 + -1Y
5X + -3Z = 1 + -1Y

Add '3Z' to each side of the equation.
5X + -3Z + 3Z = 1 + -1Y + 3Z

Combine like terms: -3Z + 3Z = 0
5X + 0 = 1 + -1Y + 3Z
5X = 1 + -1Y + 3Z

Divide each side by '5'.
X = 0.2 + -0.2Y + 0.6Z

Simplifying
X = 0.2 + -0.2Y + 0.6Z

See similar equations:

| 55XY-3Z=1 | | z2+1=9 | | 4(-2)-3(-3)+2(2)= | | 3x+18+2=5x-4 | | 3x^2-6x-7=11 | | 3X-2Y+2=4 | | n5-4=11 | | (3x/8)+6=(1/5) | | 32=10-5h+2 | | X^3+5x=6x | | 17c+8=-3c-25 | | m-7=9-13 | | 12x-106-x=37 | | -x+20=28 | | 7x+6=9x+8 | | -16t^2+300t-900=0 | | P=b+3c+3c | | ac-c=3b-4 | | x^2-8x+16=00 | | X+15=2x+50 | | 2+(1.5p)=2.5(1p) | | 0 = h-2+ 2 | | 9x+5x-108=88 | | -3/7=-n/14 | | 22x+35=21x+85 | | 15(-2b-6)=90 | | 2p+4=6 | | 11v-9v=10 | | 12-3(-4)=-6(-4) | | 2w+4xy=9zx-11 | | 4(-2)-9+4= | | 7(z)=3969 |

Equations solver categories